Distribution of the product of independent extended beta variables (2014)
ABSTRACT: The extended beta type 1 distribution has the probability density function proportional to x α−1 (1−x) β−1 exp[−σ/x(1−x)], 0 < x < 1. In this article, we derive the probability density function of the product of two independent random variables each having an extended beta type 1 distribution. We also consider several other products involving extended beta type 1, beta type 1, beta type 2, beta type 3, Kummer-beta and inverted gamma variables.